Knowledge and Practice of Menstrual Regulation (MR) in Bangladesh: Patterns and Determinants - Alam, Md. Zakiul; Sultan, Shafayat (Journal of Population and Social Studies [JPSS], 2019)
Menstrual regulation (MR) is often used as a substitute for abortion in Bangladesh. This study attempts to assess the patterns and determinants of the knowledge and practice of MR in that country. Data from the nationally representative cross-sectional Bangladesh Demographic and Health Survey 2001-2014 were employed and both bivariate and multivariable analyses were used. The findings show that both the knowledge and practice of MR is decreasing in Bangladesh. The knowledge of MR was about 82% in 2004, but it dropped to 45% in 2014. The prevalence of MR was 6.4% in 2011, but it decreased to 5.5% in 2014. The incidence of MR was 2.1% in 2011, which fell to 1.4% in 2014. Age, region, place of residence, wealth index, access to media, and use of contraception appeared to be significant determinants of MR. In order to reduce the frequency of MR being used as a form of contraception, this study highlights the necessity to emphasize the delivery of family planning services in Bangladesh to ensure the utilization of alternative modes of contraception.